2019
DOI: 10.1002/ca.23516
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Ultrasonography‐Based Investigation to Localize the Arteries on the Central Forehead Region During the Glabellar Augmentation Procedure

Abstract: Glabellar augmentation is one of the most popular cosmetic procedures but can entail severe complications caused by inadvertent intravascular injection of filler. Nevertheless, few studies have investigated the arteries on the glabellar and central forehead regions. The aim of this study was to correlate the topography and location of the arteries in this area with anatomical landmarks to propose a safety guideline. Two methods were used to investigate the glabellar and central forehead areas: dissection of 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Various materials have been proposed for use in minimally invasive forehead augmentation, such as autologous fat, HA fillers, calcium hydroxyapatite, and combinations of these [2] [5] [6] [7]. In our study, CHAP-HA Blink was selected for its low G' and viscosity, superior moldability, and shape retention capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various materials have been proposed for use in minimally invasive forehead augmentation, such as autologous fat, HA fillers, calcium hydroxyapatite, and combinations of these [2] [5] [6] [7]. In our study, CHAP-HA Blink was selected for its low G' and viscosity, superior moldability, and shape retention capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is no consensus on injection technique for safe forehead augmentation. For injections into the glabella, Phumyoo et al suggested a safe technique based on topography, a thorough understanding of arterial distribution, and color Doppler ultrasonographic examination before injection to minimize the risk of severe complications [2]. Kim proposed a novel forehead classification system based on East Asian ethnicity and suggested that first injecting a tumescent solution and then using a minimal number of entry points for the injection of filler reduces the risk of embolization [5].…”
Section: Introductionmentioning
confidence: 99%
“…ultrasound allows visualization of arteries with a diameter ≥ 0.3 mm. However, the authors used a linear transducer with a frequency of up to 12 MHz (14) . It seems that the use of a transducer with a higher frequency (18-22 MHz) allows for visualization of vessels with a diameter of about 0.1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…At the level of the glabellar point, the horizontal distances from the midline to the arteries were 4.7 mm (central artery), 7.8 mm (paracentral artery), and 14.7 and 19.2 mm (superficial and deep branches of supratrochlear artery). The depths from the skin of the arteries were between 3.1 mm (central artery) and 5.9 mm (deep branches of supratrochlear artery) 11 …”
Section: Danger Zonesmentioning
confidence: 99%
“…Injections on the nose had a high risk of vascular compromise of ophthalmic artery, while injections of the glabella more often resulted in central retinal artery compromise 13 . These studies suggest that glabellar augmentation with filler injection is one of the most dangerous procedures 11 …”
Section: Danger Zonesmentioning
confidence: 99%